Chapter Gerasim Zelić - Homo Mediterraneus? - Roksandić, Drago (Biblioteca di Studi Slavistici, 2019)
While travelling across Europe, the enlightened Orthodox monk Gerasim Zelić mentally never abandons his native Dalmatia. Moving from his Žitije, which is essentially a travelogue, the paper aims to analyse the tension between the open-minded, secular Zelić and the other Zelić, who identified himself with the Orthodox traditions of Dalmatia without knowing how to adjust them to modernity. According to the author, his rational head and his romantic heart make his global outlook deeply controversial and his mentality typical of a Homo Mediterraneus.